Hama Dan Penyakit Anakan Balangeran (Shorea balangeran (Korth.) Burck) Di Persemaian Yayasan Borneo Orangutan Survival Kabupaten Kapuas Kalimantan Tengah: Pest And Disease of Balangeran Families (Shorea Balangeran Korth.) Burck) At the Borneo Orangutan Survival Oundation Nursery. Kapuas District - Kristiana Firdara, Eritha; Rotinsulu, Johanna Maria; Syahnun, Martasya; Alpian, Alpian; Toni, Hendra; Rosdiana, Rosdiana; Penyang, Penyang (JURNAL HUTAN TROPIKA, 2025)
This study aims to identify the types of pests and diseases on Balangeran (Shorea balangeran (Korth.) Burck) saplings and analyse the frequency of attacks, intensity of attacks and the level of damage caused by pests and diseases on Balangeran saplings at the Borneo Orangutan Survival Foundation Nursery. The sampling method was simple random sampling with a total sample size of 400 balangeran seedlings. The results showed that the pests were Caterpillar (Orgyia detrita), Wood grasshopper (Valanga nigricornis), Green steamed grasshopper (Atractomorpha crenulata), Swallowtail (Leptocorisa acuta Thunberg.) while the disease was leaf spot caused by pathogens Colletotrichum acutatum, Colletotrichum gloeosporioides and Nigrospora sp. The frequency of pest attacks on balangeran was 30% with an attack intensity of 6%, the frequency of disease attacks on balangeran was 43% with an attack intensity of 10.7%, the frequency of combined attacks on balangeran was 9% with an attack intensity of 1.7%.